GROUPS WITH NORMALITY CONDITIONS FOR UNCOUNTABLE SUBGROUPS. (18th October 2021) - DE FALCO, M.; DE GIOVANNI, F.; MUSELLA, C.
Abstract: This paper continues the investigation of the structure of uncountable groups whose large subgroups are normal. Moreover, we describe the behaviour of uncountable groups in which every large subgroup is close to normal with the only obstruction of a finite section.